Spider Silk as a Next Generation Biomaterial: Advances in Biomedical and Tissue Engineering Applications - Shravanilakshmi V; Tejaswini A S; Shwetha G V; Kaveri Aramani; Gagana Sindhu S; Veenita M K (Archives of Current Research International, 2025)
Spider silk has emerged as one of the most remarkable natural protein fibres with exceptional mechanical and biological properties positioning it as a highly promising biomaterial in biomedical and tissue engineering. Its unique combination of high tensile strength, elasticity, toughness, biocompatibility and slow degradation distinguishes it from other biopolymers such as collagen, polylactic acid and gelatin. Historically employed for wound healing and suturing, spider silk has now advanced into modern applications including tissue scaffolds, wound dressings, drug delivery systems and reconstructive medicine. Recent progress in molecular biology and recombinant DNA technology has enabled artificial synthesis of silk proteins with customizable properties. Furthermore, novel functionalization such as antimicrobial activity, self-healing behaviour and facilitation of biomineralization have broadened its biomedical potential. Despite these advances, barriers remain in replicating the natural spinning process, achieving cost-effective production and ensuring clinical translation. This review provides a comprehensive overview of the production strategies, structural and functional properties and emerging biomedical applications of spider silk with emphasis on its role in regenerative medicine and tissue engineering highlighting future challenges and opportunities for its clinical adoption.